Biological activity of biomass, phycocyanin and exopolysaccharides from a native strain of Spirulina subsalsa, grown in low cost saline medium - Lolymar Romero Maza; Miguel Guevara Acosta; Bladimir Gómez Marval; Vilma Lanza Castillo (Revista Colombiana de Biotecnología)
To evaluate the biological activity of biomass, phycocyanin extracts, and exopolysaccharides from S. subsalsa, axenic cultures were conducted at 9 ‰ salinity by adding seawater and using a low-cost saline medium: [N]=14 mM. The cultivation was performed in an external environment and was manually stirred. The cyanobacteria were centrifuged when they reached the exponential and stationary growth phases. The filtrate was used to obtain the exopolysaccharides by acetone precipitation, and the biomass was used to obtain the extracts in the different solvents. Phycocyanin was extracted in water. The activity against Escherichia coli, Pseudomonas aeruginosa, Bacillus cereus, Micrococcus luteus and Staphylococcus aureus, using the agar diffusion technique was evaluated. The results showed that only the ethanolic biomass extracts, harvested in stationary phase, had mild to moderate antibacterial activity against Bacillus cereus and Staphylococcus aureus. The antifungal effect of the extracts was also evaluated. The aqueous extracts (exopolysaccharides and phycobiliproteins) and ethanolic, chloroformic and hexane extracts of S. subsalsa, did not inhibit the growth of Rhizopus orizae and Aspergillus niger. The toxicity of the extracts was tested using the crustaceans Artemia franciscana and Daphnia magna. The extracts of exopolysaccharides and biomass were found to be innocuous, but the aqueous extracts of phycocyanin showed significant cytotoxic activity against A. franciscana (LC50 exponential phase= 1.69 μg mL-1; LC50 stationary phase= 2.59 μg mL-1). The results suggest that the native strain of S. subsalsa, cultivated in a seawater enriched medium and in a low-cost saline medium has potential to produce bioactive compounds with antimicrobial properties.